Mesenchymal Stem Cell-Derived Extracellular Vesicles for Corneal Wound Repair - Hongyan Tao; Xiaoniao Chen; Hongmei Cao; Lingyue Zheng; Qian Li; Kaiyue Zhang; Zhibo Han; Zhong-Chao Han; Zhikun Guo; Zongjin Li; Liqiang Wang (Stem Cells International)
With the immunoregulation potential, mesenchymal stem cells (MSCs) have been used for tissue regeneration by relieving inflammation in the injured tissues. When this repair process is interfered by immune disorders or pathological angiogenesis, the delays in corneal epithelial wound healing can lead to a persistent epithelial defect. Stem cell-derived extracellular vesicles (EVs), which carry abundant bioactive molecules from stem cells, have provided an alternative to regeneration therapy. In this study, we aimed to investigate if EVs from human placenta-derived MSCs (hP-MSCs) could ameliorate alkali injury of the cornea in the mouse model. 33.33 μg/μL EVs in 10 μL PBS were applied to the cornea. Repeat application three times, and 100 μg EVs (in 30 μL PBS) in total were administrated per day for two weeks. Our results revealed that EVs from hP-MSCs had preferable functions including enhancing proliferation and anti-inflammation and suppressing apoptosis of corneal epithelial cells. Furthermore, hP-MSC-derived EVs ameliorated mouse corneal wound healing by inhibiting angiogenesis and inflammation. Taken together, our current data suggested that hP-MSC-derived EVs have the beneficial effects of corneal wound healing, which provide alternative cell-free therapy with great practical value.